2021
DOI: 10.46912/jbrcp.224
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Mental Illness among Women Admitted in a Rehabilitation Center in Jos, Nigeria: A 5-Year Profile

Abstract: Substance use disorder are among the most common public health problems caused by using legal and/or illegal substances. Therefore, this study is aimed at reviewing a five-year profile of women admitted at a rehabilitation center in Jos, Nigeria for substance use and mental illness. This is a retrospective cross-sectional study carried out on 183 females admitted between 2012 and 2017 at a rehabilitation center in Jos, Nigeria. Data collection was carried out from documents note of these female participants. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Notwithstanding these factors, these ndings may help support the case for equal prioritisation of both adolescent girls and young women's mental needs. For instance, another study found the prevalence of depressive disorder in young women (ages 20 to 29) in a rehabilitation centre to be 36.1% in Nigeria [34]. The argument could be made that substance abuse increases the risk of mental health issues.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Notwithstanding these factors, these ndings may help support the case for equal prioritisation of both adolescent girls and young women's mental needs. For instance, another study found the prevalence of depressive disorder in young women (ages 20 to 29) in a rehabilitation centre to be 36.1% in Nigeria [34]. The argument could be made that substance abuse increases the risk of mental health issues.…”
Section: Demographic Factorsmentioning
confidence: 99%